L’image de la « belle Gitane » dans la littérature romantique allemande et française - Le Trionnaire-Bolterauer, Alice (Romanica Silesiana)
The Image of the “Beautiful Gypsy Woman” in German and French Literature of Romanticism In my article I try to analyze the image of the “beautiful gypsy woman” on the basis of four literary texts from the period of Romanticism. The image, in fact, is an invention of the Romantic period, and is discussed here as the reflection of a changing female identity. Male authors respond to the demands of a new generation of women by creating new representations of femininity which, on the one hand, are fascinating and, on the other, quite threatening. The figure of the beautiful, but “foreign” woman is where these authors locate their dreams and fears. Key words: Gypsy, Romantic literature, image of women, sexuality, emancipation.